PENGARUH PAKET PEMBELAJARAN PENDIDIKAN LINGKUNGAN HIDUP DAN GAYA KOGNITIF TERHADAP KEMAMPUAN MEMECAHKAN MASALAH LINGKUNGAN (Studi Eksperimen pada Jurusan Kimia, FMIPA Universitas Negeri Jakarta) - Agung Purwanto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2012)
The objective of the research was aimed at finding out whether there is effect of the environmental education learning package and cognitive style on environmental problem solving skills. This research conducted was exsperiment methode. The target of population is the students at the Mathematics and Natural Sciences at the State University of Jakarta. Then accessible of population is Department of Chemistry and take it by randomly (n=40).The research came five conclusions are follow: the first, as a whole the ability of students problem-solving learning environment in an integrated package of environmental education is high than the monolithic environmental education learning package; the second, the ability of students problem-solving learning environment in field independent style cognitive is not high than the field dependent style cognitive; the third, interaction effect between learning and cognitive styles environmental education package; the fourth, the ability of students to solve environmental problems based on cognitive style of field dependent on an integrated learning package environmental education lower than on learning environmental education monolithic package, and the five, there is the ability of students to solve environmental problems based on field independent cognitive styles in an integrated learning package environmental education is high than on learning environmental education monolithic package.